2007
DOI: 10.1136/gut.2006.117390
|View full text |Cite
|
Sign up to set email alerts
|

Increased colonic pain sensitivity in irritable bowel syndrome is the result of an increased tendency to report pain rather than increased neurosensory sensitivity

Abstract: Objective: The aim was to determine whether lower visceral pain thresholds in irritable bowel syndrome (IBS) primarily reflect physiological or psychological factors. Methods: Firstly, 121 IBS patients and 28 controls underwent balloon distensions in the descending colon using the ascending methods of limits (AML) to assess pain and urge thresholds. Secondly, sensory decision theory analysis was used to separate physiological from psychological components of perception: neurosensory sensitivity (p(A)) was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 45 publications
9
118
3
5
Order By: Relevance
“…As our patients were recruited from hospitals and not from the primary health care, we can suspect them to have a more severe disease (1). Thus, the histological picture may be of minor importance in IBS compared to cognitive and psychosocial functions (21), explaining the impaired psychological well-being and more pronounced symptoms in our IBS patients, although similar histopathology. The discussion above is provided that idiopathic IBS is the same as IBS associated with MC and IBD.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As our patients were recruited from hospitals and not from the primary health care, we can suspect them to have a more severe disease (1). Thus, the histological picture may be of minor importance in IBS compared to cognitive and psychosocial functions (21), explaining the impaired psychological well-being and more pronounced symptoms in our IBS patients, although similar histopathology. The discussion above is provided that idiopathic IBS is the same as IBS associated with MC and IBD.…”
Section: Discussionmentioning
confidence: 92%
“…However, the increased colonic sensitivity in idiopathic IBS is more influenced by a psychological tendency to report pain than neurosensory sensitivity (21). Irritable bowel syndrome does have a peripheral component, but the central components become more prominent as disease severity increases (22).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with "rapid phasic distension", which mainly stimulates the intestinal serosa receptors, the main effect of AML is through the stimulation of the intestinal mucosa and submucosa receptors. These receptors are involved in different nerve conduction pathways while also participating in intestinal perception (Mertz et al, 1995;Dorn et al, 2007). Visceral hypersensitivity is a biological marker in some IBS cases, especially D-IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects and study design have been previously reported, 19,20 but the hypothesis that there are age-related differences in ANS activity and its response to meals and intraluminal distention has not been described previously. 19,20 Subjects were recruited via advertisements or physician referrals and screened by telephone. The study population consisted of 156 patients who fulfilled the Rome III criteria for IBS, had received a physician diagnosis of IBS, and had current symptoms (abdominal pain or discomfort at least 3 days per month in the last 3 months).…”
Section: Subjectsmentioning
confidence: 99%